PENGARUH RISIKO PEMBIAYAAN DAN PROPORSI PEMBIAYAAN NON INVESTASI TERHADAP PROFIT DISTRIBUTION MANAGEMENT PERBANKAN SYARIAH - Martika, Lia Dwi (Program Studi Akuntansi, Universitas Kuningan, 2017)
ABSTRACTIslamic banks should be able to maintain the confidence of depositors to keep their funds in Islamic banks. One effort to do that is through the profit distribution management as well as possible so that depositors in Islamic banks keep their money in the bank. Profit Distribution Management (PDM) is an activity performed managers to manage the distribution of profits to fulfill responsibility of profit sharing Islamic banks to their depositors. The purpose of this research to analyze the influence of Risk Financing and Non Investment Financing Proportion toward Profit Distribution Management. This research was conducted in Islamic banks exist in Indonesia, Malaysia and the countries which are Gulf Cooperation Council (GCC). The sampling technique used was purposive sampling. Analysis of the data used is descriptive quantitative method and statistical analysis used panel data multiple regression with Eviews program. The test results showed risk financing significantly positive influence the profit distribution management. The results of hypothesis testing also found that the proportion of non-investment financing no significant effect on the profit distribution management in Islamic banks in Indonesia, Malaysia and the countries which are Gulf Cooperation Council (GCC).Keywords : Risk Financing, Non Investment Financing Proportion, Profit Distribution Management, Islamic banks in Indonesia, Malaysia and GCC.